Kepemimpinan Kepala Sekolah Dalam Mewujudkan Merdeka Belajar di Sekolah Menengah Pertama - Budiwati, Susi; Sumiati, Ati; Sururi, S (Universitas Pendidikan Indonesia, 2024)
This research aims to analyze the distribution of research articles with the theme of school principal leadership in realizing an independent learning curriculum in junior high schools. VosViewer is used as an analysis tool in research and uses a bibliometric approach. Article references were obtained from Google Scholar with the support of the publish or perish program, and 998 articles were found that were considered relevant to the related topic. The research period used for documents indexed by Google Scholar is from 2019 to 2024. The research results are focused on finding and analyzing topics that are related to principal leadership and other data analysis. Keywords regarding principal leadership in junior high schools are associated with 4 clusters with a total of 189 links and 1754 total link strengths. The results of the analysis of the development of publications in the 2019–2024 period show that research on the theme of kiai decision-making in Islamic boarding schools has been studied quite a lot by researchers on principal leadership and freedom to learn. The highest number of publications in 2023 will be 14 articles, and the least in 2024 will be 6 articles. This topic is an interesting thing to continue to be researched by future researchers. This is due to the graph of the increase in this theme every year, which indicates that research topics relating to principal leadership and freedom of learning are increasingly of interest to researchers. This will have a significant impact and be very important for the future development of the school.